2019
DOI: 10.1016/j.jctube.2019.100093
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and its effective factors in tuberculosis patients receiving directly observed treatment short-course (DOTS)

Abstract: BackgroundQuality of life in patients affected with chronic diseases has developed into a therapeutic objective as the best tool to evaluate response to treatment and medical care. The purpose of this study was to evaluate quality of life and its related factors in tuberculosis patients receiving directly observed treatment short-course in Iran.MethodsThis was a cross-sectional research with a descriptive-analytic design. Sample size included 71 patients affected with tuberculosis based on census method; so th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 15 publications
0
26
1
3
Order By: Relevance
“…This behavior, however, should be mitigated as low adherence or non‐adherence to TB‐DOTS regimen negatively affects the patient, their loved ones, and the healthcare sector. Patients who are non‐adherent to TB medications increases the risk for drug resistance thus, leading to prolonged infectivity (O'Donnell, Wolf, Werner, Horsburgh, & Padayatchi, ) and poor quality of life (Salehitali, Noorian, Hafizi, & Dehkordi, ). The loved ones of the infected patient who live with them in the same household may also contract the disease thus, affecting the overall health status and productivity of the family (Chorba & Jereb, ).…”
Section: Discussionmentioning
confidence: 99%
“…This behavior, however, should be mitigated as low adherence or non‐adherence to TB‐DOTS regimen negatively affects the patient, their loved ones, and the healthcare sector. Patients who are non‐adherent to TB medications increases the risk for drug resistance thus, leading to prolonged infectivity (O'Donnell, Wolf, Werner, Horsburgh, & Padayatchi, ) and poor quality of life (Salehitali, Noorian, Hafizi, & Dehkordi, ). The loved ones of the infected patient who live with them in the same household may also contract the disease thus, affecting the overall health status and productivity of the family (Chorba & Jereb, ).…”
Section: Discussionmentioning
confidence: 99%
“…This study also found respondents who experience moderate-to-severe stress levels with good quality of life, this is because patients have the ability and opportunity ICHT 2019 to deal with and control the conditions they experience, so that people can maintain their quality of life in a more positive direction. This is also influenced by interpersonal factors, including social relations in the family Because social support, family, relatives, and peers can make a person's quality of life good [10]. This study also found respondents who experienced moderate-to-severe stress levels with poor quality of life.…”
Section: Discussionmentioning
confidence: 53%
“…ShahriarSalehitali et al, [19] and Patel PG et al, [20] had conducted a similar study but obtained different results. Shariariarconcluded that Gender and residential area were signi icant in causing PTB, whereas, Patel concluded that Gender, SES and age were not a signi icant association in causing PTB.…”
Section: Discussionmentioning
confidence: 95%